Influences of four weeks intermittent hypoxic training on aerobic ability of high-level race walking athletes - Chen, Y.; Qiu, J.; Yi, L.; Wang, L.; Zou, M. (Exercise Biochemistry Review, 2018)
Objective Altitude training is an important training method for endurance athletes to improve aerobic capacity. Endurance athletes take advantage of the dual stimulation of hypoxia in the altitude environment and hypoxic during training to improve their exercise capacity and physiological function. However, due to the high stimulation of altitude training, the difficulty of recovery and other characteristics, and with the appearance of hypoxic installation, a series of new training methods have been developed.